DESEMPEÑO ORGANIZACIONAL DE MICROEMPRESAS EN MÉXICO - Maria del Carmen Gutiérrez-Diez; Alma Lilia Sapién-Aguilar; Laura Cristina Piñón-Howlet (European Scientific Journal, ESJ, 2013)
Micro enterprises as the backbone of national economies suffer from serious shortcomings. Therefore, diagnosing organizational performance is vital to help them. This paper made a diagnosis in 69 micro enterprises from the tourism sector at Tapachula, Chiapas, México. It was a directed and non-probabilistic sample. The instrument that was developed consisted of 46 questions, of which 22 were yes or no questions, and the remaining responses were open to different perspectives according to the factors to be evaluated: information and communication technologies, quality, training and management. The data was collected between 2010 and 2011. The results showed that SMEs studied have the same characteristical problems known in this sector: lack of technology, no training, a basic grasp of the quality concept and poor management.